Structural insights into transcription regulation of the global OmpR/PhoB family regulator PhoP from Mycobacterium tuberculosis - Jing Shi; Zhenzhen Feng; Qian Song; Aijia Wen; Tianyu Liu; Liqiao Xu; Zonghang Ye; Simin Xu; Fei Gao; Liuxiang Xiao; Jiapeng Zhu; Kalyan Das; et al. (Nature Communications)
Abstract As a global transcription activator or repressor, the representative OmpR/PhoB family response regulator PhoP plays a crucial role in regulating bacterial pathogenicity and stress adaptation. However, the molecular mechanisms underlying the transcriptional regulation that define its differential functions remain largely unclear. In the present study, we determine three cryo-EM structures of Mycobacterium tuberculosis (Mtb) PhoP-dependent transcription activation complexes (PhoP-TACs) and build one preliminary cryo-EM structure model of Mtb PhoP-dependent transcription repression complex (PhoP-TRC). In PhoP-TACs, tandem PhoP dimers cooperatively recognize various types of promoters through conserved PhoP-PHO box interactions, which displace the canonical interactions between the -35 element and σAR4 of RNA polymerase (RNAP), unraveling complex transcription activation mechanisms of PhoP. In PhoP-TRC, one PhoP dimer binds and significantly distorts the upstream PHO box of the promoter cross-talked with the global nitrogen regulator GlnR through the PhoP-PHO box, PhoP-GlnR and αCTD-DNA interactions. This unique binding of PhoP creates steric hindrances that prevent additional GlnR binding, positioning PhoP within a unique ‘competitive occluding model’, as supported by prior biochemical observations. Collectively, these findings reveal the dual molecular mechanisms of PhoP-dependent transcription regulation, and offer valuable insights for further exploration of the enormous PhoP-like OmpR/PhoB family response regulators.